Subsequent treatment of leafy vegetables with low doses of UVB-radiation does not provoke cytotoxicity, genotoxicity, or oxidative stress in a human liver cell model. (October 2021) - Wiesner-Reinhold, Melanie; Dutra Gomes, João Victor; Herz, Corinna; Tran, Hoai Thi Thu; Baldermann, Susanne; Neugart, Susanne; Filler, Thomas; Glaab, Johannes; Einfeldt, Sven; Schreiner, Monika; Lamy, Evelyn
Abstract: Ultraviolet B (UVB) radiation in low but ecological-relevant doses acts as a regulator in the plant's secondary metabolism. This study investigates the effect of UVB radiation from light-emitting diodes (LEDs) [peak wavelength of (290 ± 2) nm] on the biosynthesis of health-promoting secondary plant metabolites (carotenoids, phenolic compounds, and glucosinolates) of green and red leafy vegetables of Lactuca sativa, Brassica campestris, and Brassica juncea followed by evaluation of potential adverse effects in a human liver cell model. UVB radiation led to a significant increase in individual secondary plant metabolites, especially of phenolic compounds and glucosinolates, e.g. alkenyl glucosinolate content. Kaempferol und quercetin glycoside concentrations were also significantly increased compared to untreated plants. The plant extracts from Lactuca sativa, Brassica campestris, and Brassica juncea were used to assess cytotoxicity (WST-1 assay and trypan blue staining), genotoxicity (Comet assay), and production of reactive oxygen species (EPR) using metabolically competent human-derived HepG2 liver cells. No adverse effects in terms of cytotoxicity, genotoxicity, or oxidative stress were detected in an extract concentration ranging from 3.125 to 100 μg ml −1 . Notably, only at very high concentrations were marginal cytostatic effects observed in extracts from UVB-treated as well as untreated plants. In conclusion, the application of UVB radiation from LEDs changes structure-specific health-promoting secondary plant metabolites without damaging the plants. The treatment did not result in adverse effects at the human cell level. Based on these findings, UVB LEDs are a future alternative, promising light source to replace currently commonly used high-pressure sodium lamps in greenhouses.